The Interrelationship between Coping Strategies and Socio-Psychological Competency of University Students’ Personality - Romanova, Anzhela V. (2020)
In contemporary society characterized by socio-economic and political instability, the problem of studying the factors and mechanisms that contribute to the constructive resolution of life difficulties and counteracting their negative consequences is very important. This paper contains the results of an empirical study of the characteristics and relationships of students’ coping behavior with different levels of their socio-psychological competency. The research methods comprised the following: theoretical analysis, empirical research (testing), qualitative analysis of the obtained data, mathematical and statistical data processing (SPSS Statistics, Excel). The characteristics of indicators of socio-psychological competency were determined with the use of the technique for assessing socio-communicative competency, as well as a questionnaire that reveals the possibility of using socio-psychological skills by a person in difficult life situations. To study coping behavior, the following were used: “The ways of coping questionnaire” and “The youth coping scale”. The validity and reliability of the research results was ensured by the initial methodological positions, the use of tested tools, representativeness of the research sample, as well as mathematical processing of data with the help of software package for statistical analysis. The conclusions have been drawn that the basis of constructive mechanisms to overcome difficult life situations is a high level of formation of professional skills and abilities, introversion, motivation to achieve success, high intellectual development, moral standards, a high level of development of communication skills. It is these mechanisms that make it possible to resolve problem situations and tasks at work in a productive way. Their absence or a low level of development contributes to the dominance of situational methods of overcoming difficult life situations that impede professional formation and personal development.